Isovitexin Inhibits Ginkgolic Acids-Induced Inflammation Through Downregulating SHP2 Activation - Zhang, Yiwei; Qi, Zhipeng; Wang, Wenjie; Wang, Lei; Cao, Fuliang; Zhao, Linguo; Fang, Xianying (Frontiers in Pharmacology, 2021)
It has been reported that Celtis sinensis Pers. is employed as a folk medicine for the treatment of inflammatory diseases. But the mechanism supporting its use as anti-inflammatory remains unclear. To investigate the anti-inflammatory of Celtis sinensis Pers. ICR mice were provided Celtis sinensis Pers. leaf extract (CLE) at 100, 200mg/kg after ginkgolic acids (GA) sensitization. Our data showed that CLE and the main flavonoid isovitexin in CLE could ameliorate GA-induced contact dermatitis in mice. Ear swelling, inflammatory cell infiltration and splenomegaly were inhibited significantly by isovitexin, while the weight loss of mice in the isovitexin-treated group was much better than that in the dexamethasone-treated group (positive control drug). It has been reported in previous research that GA-induced inflammation is closely related to the T cell response. Therefore, T cells were the focus of the anti-inflammatory effect of isovitexin in this paper. The in vivo results showed that isovitexin (10, 20mg/kg) inhibited the expression of proinflammatory cytokines (TNF-α, IFN-γ, IL-2 and IL-17A) in lymph nodes, inhibited the secretion of cytokines into the serum from mice with contact dermatitis and promoted the expression of apoptosis-related proteins. In vitro, isovitexin also induced apoptosis and inhibited proinflammatory cytokine expression in Con A-activated T cells. Further study showed that the MAPK and STAT signaling pathways and the phosphorylation of SHP2 were inhibited by isovitexin. Both molecular docking and biological experiments indicated that SHP2 may be an anti-inflammatory target of isovitexin in T cells. Taken together, isovitexin can serve as a potential natural agent for the treatment or prevention of GA-induced inflammatory problems.